Tourism Development Strategies in Menganti Beach, Kebumen - Octanisa, Dheanita Sekarini; Palestho, Andrea Basworo; Pratiwi, Yunisti (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
The tourism industry is one of the largest industries globally in the world both in terms of the number of actors and the money circulating in it. It was recorded that around 1.50 billion world tourists traveled in 2019. This research aims to know the tourism development strategies in Menganti Beach based on the level of tourist satisfaction. his research is based on descriptive quantitative method. The data used in this study are qualitative and quantitative data that obtained through literature study, observation, interviews and questionnaires to 100 respondents who had experienced on visiting Menganti Beach. Data were analyzed using Importance Performance Analysis (IPA) and supported by descriptive analysis methods. The results showed that the development strategy is formulated by improving the performance of quadrant I elements that are also the weaknesses of the destination, maintaining the elements of quadrant II which are also the strengths of the destination, and paying attention to the opportunities and threats that the destination has. The development strategy is broadly emphasized on the aspects of strengthening, developing and packaging tourist attractions, maintaining infrastructure performance, improving the quality and quantity of tourism supporting facilities, increasing marketing (promotion), improving the quality of human resources in the field of tourism services, improving organizational and governance systems and developing partnership relation.